The Economic Burden of Colorectal Cancer in Type 2 Diabetes Mellitus (T2DM) in Shanghai, China - Zhi‐xu Zhu; Yu‐xin Peng; Jing‐hong Ye; Yan Wei (Cancer Medicine)
ABSTRACT Objective This study aimed to analyze disease cost levels among colorectal cancer (CRC) patients, examining differences in disease costs between those with type 2 diabetes mellitus (T2DM) and those without T2DM while considering various demographic characteristics. Methods The study included respondents from colorectal cancer patients diagnosed and managed within the population‐based cancer registry system of the Shanghai Municipal Center for Disease Control and Prevention from 2020 to 2022. Diabetic colorectal cancer cases were matched with nondiabetic colorectal cancer controls using propensity scores, maintaining a 1:1 ratio between cases and controls; bias for the majority of the matched variables is below 10%. Direct, indirect, and intangible costs were estimated for study subjects. Results After propensity score matching, the analysis encompassed 376 cases of T2DM‐related CRC and 376 non‐T2DM CRC cases. The T2DM group exhibited higher direct medical costs (¥57,059.65 vs. ¥48,933.93, p < 0.05), direct nonmedical costs (¥9292.45 vs. ¥7969.35), indirect costs (¥300.13 vs. ¥241.11), intangible costs (¥3601.70 vs. ¥2631.96), and total disease costs (¥70,253.93 vs. ¥59,776.36, p < 0.05) compared to the non‐T2DM group. In Stage II CRC, direct medical costs were ¥74,008.39 for the T2DM group versus ¥57,368.84 for the non‐T2DM group. Among surgical patients, direct medical costs were ¥57,658.81 for the T2DM group versus ¥1337.00 for the non‐T2DM group, and ¥49,061.52 for the non‐T2DM surgical group versus ¥1089.00 for the non‐T2DM nonsurgical group. Conclusion Colorectal cancer imposes a substantial economic burden. Patients with CRC and concurrent T2DM experience a higher economic burden compared to nondiabetic patients. Notably, individuals with both T2DM and Stage II cancer face a significantly higher economic burden, whereas surgical patients exhibit a significantly greater disease burden than nonsurgical patients. Efforts should concentrate on primary prevention and secondary prevention to alleviate the economic burden associated with colorectal cancer.